2007
DOI: 10.1128/mcb.01883-06
|View full text |Cite
|
Sign up to set email alerts
|

The E295K DNA Polymerase Beta Gastric Cancer-Associated Variant Interferes with Base Excision Repair and Induces Cellular Transformation

Abstract: 14350-14355, 2005). In the work described here, we show that the E295K gastric carcinoma pol ␤ variant acts in a dominant-negative manner by interfering with base excision repair. This leads to an increase in sister chromatid exchanges. Expression of the E295K variant also induces cellular transformation. Our data suggest that unfilled gaps are channeled into a homology-directed repair pathway that could lead to genomic instability. The results indicate that base excision repair is critical for maintaining gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
147
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(153 citation statements)
references
References 40 publications
6
147
0
Order By: Relevance
“…Leu22Pro tumor-associated variant of polβ is dRP lyase deficient (Dalal et al, 2008). It is being reported that the E295K mutation in polβ which is a gastric cancer-associated variant interferes with base excision repair and induces cellular transformation (Lang et al, 2007). Therefore, any kind of point mutation or large deletion can change the conformation during the polymerase opening and thereby altering the DNA positioning in the active site (Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leu22Pro tumor-associated variant of polβ is dRP lyase deficient (Dalal et al, 2008). It is being reported that the E295K mutation in polβ which is a gastric cancer-associated variant interferes with base excision repair and induces cellular transformation (Lang et al, 2007). Therefore, any kind of point mutation or large deletion can change the conformation during the polymerase opening and thereby altering the DNA positioning in the active site (Yang et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The Val246 variant was shown to mis-incorporate nucleotides through altered DNA positioning in the active site (Dalal et al, 2008). It was evidenced that expression of the E295K gastric carcinoma-associated pol beta variant (Lang et al, 2007) in mouse cells interferes with BER and induces sister chromatid exchanges and cellular transformation (Lang et al, 2007). An 87-bp deletion variant of polβ that has been found to be associated with breast, lung (Bhattacharyya and Banerjee 1997;Bhattacharyya et al, 1999a), colon, kidney, prostate cancer, has been shown to act as a dominant negative mutant (Bhattacharyya et al, 1999;Chen et al, 2000;Bhattacharyya et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Data represent the mean of three independent experiments with error bars showing SEM. (B and C) Base excision repair assays of MEF cell extracts using either a Uracil (B) or hypoxanthine (C) substrate as described previously (12). BER assays were carried out as described in Experimental Procedures.…”
Section: Discussionmentioning
confidence: 99%
“…MEF extracts were prepared as described previously, and base excision repair assays were conducted with either a UDG or hypoxanthine substrate as described previously (12). BER reactions were quenched by addition of an equal volume of formamide gel loading dye [90% (vol/vol) formamide, 0.3 M EDTA].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation